EVALUASI SISTEM INFORMASI PERIZINAN PEREKONOMIAN PADA DPMPTSP KOTA SURAKARTA MENGGUNAKAN FRAMEWORK COBIT 4.1 DENGAN MODEL MATURITY LEVELS - Nugroho, Fareza Aditiyanto; Fitriasih, Sri Hariyati; Harsadi, Paulus (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2023)
Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Surakarta is an institution that can be used as a solution by the Regional Government, especially the Surakarta City Government to overcome the problems of public services that are expected to have the competitive advantage of Surakarta City in service to the community. The forms of services provided include prime licensing and non-licensing services and one door with convenience, transparent costs, and timely completion. In addition, it is also supported by the use of an adequate Information and Information Technology System, so that the data stored and data presented are always fast, precise and accurate. The purpose of this study was to obtain knowledge about the application of an integrated service information system and to evaluate to determine whether the system was used with the existing provisions and according to procedures. Weaknesses of agencies that have never been measured by system performance in the application system. Based on the constraints that exist in the agency, the method used in this study is the COBIT 4.1 framework with the Delivery and Support domain which includes DS10 (manage problem) and DS11 (manage data). From this research produces on process DS10 count to 3.71 and DS11 count to 3.86 that describe DPMPTSP Surakarta is only at level 4 (manage level) which means the use of the system is in accordance with its functions and procedures existing and standardized in the Standard Operating System (SOP) documented and applied and formalized. The optimized procedure has been socialized to all management and employees and has been obeyed and worked on in daily activities.